Likejon: szkoła Arystotelesa w Atenach i jej pozostałości = Lyceum: Aristotle's school in Athens and its remains - Mróz, Tomasz (1975- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper aims to compile some ancient sources concerning the Aristotle's school and contemporary excavations conducted in the centre of the Athens. These excavations aim to present the remnants of the Lyceum for the needs of unprofessional audience. The location and presumable appearance of the buildings of Lyceum are presented, Plato's references to the gymnasion of Lyceum and to the Aristotle's life are discussed. Finally, controversies over the exhibition of this archeological site are presented. Some reproductions enrich the paper.
Keywords: Arystoteles (filozof; 384 p.n.e.-322 p.n.e.); Likeon; Ateny; Aristotle (384-322 BC); Lyceum; Athens